Preservation of King Oyster Mushroom by the use of different fermentation processes. Issue 1 (7th July 2017) - Zheng, Heng‐Guang; Chen, Jun‐Chen; Ahmad, Ijaz
Abstract: Three typical lactic acid fermentation processes (i.e., sauerkraut, pickling, and kimchi) were used via inoculation with the starter culture of Lactobacillus plantarum, for the purpose of preserving King Oyster Mushrooms ( Pleurotus eryngii ). Notable differences were observed in chemical composition between King Oyster Mushrooms and common vegetable plants. Despite this, LAB still quickly colonized the fruit body of King Oyster Mushroom, and rapidly controlled the spoilage and pathogenic microorganisms. The final fermented products contained high population of LAB (>7 Log cfu/g). In addition, the concentrations of nitrite in final fermented products were lower than the current maximum allowable levels (<20 mg/kg) in China. These results indicated that it is effective and safe to preserve King Oyster Mushroom by the method of lactic acid fermentation. It is concluded that for long‐term preservation of mushrooms the inoculated lactic‐acid‐fermentation method is better than the age‐old heavy‐salting method. Practical applications: Heavy salting (salt concentration ≥20%) is currently the most viable method to preserve the perishable mushroom in cultivation factories. However, to further make edible products from this salted mushroom, the excess salt must be washed out of the salted mushroom and discarded as waste. Disposal of such waste has become a costly problem for a mushroom‐cultivation company. To reduce the amount of brine waste released into the environment, introducing of lactic acid fermentation in preservation of surplus mushroom would be a good alternative for these mushroom‐cultivation companies. The present study aims to assess the safety and preservation effects of the three different fermentation processes for King Oyster Mushroom. The relevant results will help those technicians to choose the adequate fermentation methods in preservation of mushroom and also be helpful to reduce the brine sewage pollution caused by the preservation process of heavy salting.